Power, fairness and trust: understanding and engaging with vaccine trial participants and communities in the setting up the EBOVAC-Salone vaccine trial in Sierra Leone - Luisa Enria; Shelley Lees; Elizabeth Smout; Thomas Mooney; Angus F. Tengbeh; Bailah Leigh; Brian Greenwood; Deborah Watson-Jones; Heidi Larson (BMC Public Health, 2016)
Abstract Background This paper discusses the establishment of a clinical trial of an Ebola vaccine candidate in Kambia District, Northern Sierra Leone during the epidemic, and analyses the role of social science research in ensuring that lessons from the socio-political context, the recent experience of the Ebola outbreak, and learning from previous clinical trials were incorporated in the development of community engagement strategies. The paper aims to provide a case study of an integrated social science and communications system in the start-up phase of the clinical trial. Methods The paper is based on qualitative research methods including ethnographic observation, interviews with trial participants and key stakeholder interviews. Results Through the case study of EBOVAC Salone, the paper suggests ways in which research can be used to inform communication strategies before and during the setting up of the trial. It explores notions of power, fairness and trust emerging from analysis of the Sierra Leonean context and through ethnographic research, to reflect on three situations in which social scientists and community liaison officers worked together to ensure successful community engagement. Firstly, a section on “power” considers the pitfalls of considering communities as homogeneous and shows the importance of understanding intra-community power dynamics when engaging communities. Secondly, a section on “fairness” shows how local understandings of what is fair can help inform the design of volunteer recruitment strategies. Finally, a section on “trust” highlights how historically rooted rumours can be effectively addressed through active dialogue rather than through an approach focused on correcting misinformation. Conclusion The paper firstly emphasises the value of social science in the setting up of clinical trials, in terms of providing an in depth understanding of context and social dynamics. Secondly, the paper suggests the importance of a close collaboration between research and community engagement to effectively confront political and social dynamics, especially in the context of an epidemic.